Morphologic changes and clinical consequences of wide AAA necks treated with 34-36mm proximal diameter EVAR devices - Oliveira-Pinto,José (2020)
Introduction: Endovascular aneurysm repair (EVAR) became the preferred modality for infrarenal aneurysm (AAA) repair. Several available endografts have main body proximal diameters up to 36mm, allowing for treatment of proximal AAA necks up to 32 mm. However, large neck represents a predictor of proximal complications after EVAR. The purpose of this study is to evaluate mid-term outcomes of patients requiring 34-36mm main body devices. Methods: Retrospective review of a prospectively maintained database including all patients undergoing elective EVAR for degenerative AAA in a single tertiary referral hospital in The Netherlands were eligible. All measurements were performed on center-lumen line reconstructions obtained on dedicated software. Patients were classified as large diameter (LD) if the implanted device was >32mm wide. The remaining patients were classified as normal diameter (ND). Primary endpoint was neck-related events (a composite of endoleak (EL) 1A, neck-related secondary intervention or migration >5mm). Neck morphology changes and survival were also assessed. Differences in groups were adjusted by multivariable analysis. Results: The study included 502 patients (90 in the LD group; 412 in the ND group). Median follow-up was 3.5 years (1.5-6.2) and 4.5 years (2.1-7.3) for the LD and ND groups, respectively (P = .008). Regarding baseline characteristics, hypertension (83% vs 69.7%, P=.012) and smoking (86% vs 74.1%, P=.018) were more frequent in the LD group. Patients in the LD group had wider (Proximal neck Ø > 28 mm: 75% vs 3.3%, P<.001), more angulated (±-angle>45º: 21% vs 9%, P=.002), more conical (39.8% vs 20.3%, P<.001) and a thrombus-laden neck (Neck thrombus >25%: 42% vs 32.3%, P<.089). Oversizing was greater among LD group (20% [12.5-28.8] vs 16.7% [12-21.7], P=.008). All other anatomical risk factors were similar between groups. The 5-year freedom from neck-related event was 73% for the LD group and 85% for the ND group, P=.001. Type 1A endoleaks were more common in the LD group (12.2% vs 5.1%, P=.003). Migration > 5mm occurred similarly in both groups (7.8% vs 5.1%, P=.32). Neck-related secondary interventions were also more common among LD patients (13.3% vs 8.7%; P = .027). On multivariable regression analysis, LD group was an independent risk factor for neck-related adverse events (Hazard Ratio [HR]: 2.29; 95% confidence interval [CI], 1.37-3.83, P=0.002). Neck dilatation was greater among LD patients (median, 3 mm [IQR, 0-6] vs 2mm [IQR, 0-4]; P =.034) On multivariable analysis, LD was an independent predictor for neck dilatation > 10 % (HR: 1.61 CI 95% 1.08-2.39, P=.020). Survival at 5-years was 66.1% for LD and 71.2% for SD groups, P=.14. Conclusion: Standard EVAR in patients with large infrarenal necks requiring a 34to 36-mm proximal endograft is independently associated to increased rate of neck related events and more neck dilatation. This subgroup of patients could be considered for more proximal seal strategies with fenestrated or branched devices, if unfit for open repair. Tighter surveillance following EVAR in these patients in the long term is also advised.